Judicial Murders: a Report (Archives of Criminology, 1994)
The Lublin castle has historical connections with the old town area. The castle hill was the seat of a stronghold and residence of the starost who ruled in the king’s name. Excavations led to discovery of traces of a 9th century settlement.The construction of a stone castle began in the 14th century. It was used as a prison in the 19th century and until 1954.In 1939‒1944, the Lublin Castle housed a prison of the Nazi secret police and security service, the Sicherheitsdienstpolizei and Sicherheitsdienst Lublin.The role of the Lublin Castle prison was particularly dreadful; dring the period of martyrdom and extermination of the Polish nation under the Nazi occupation of  Poland. Even today, the castle is treated as a national symbol of the heroism and suffering of the Polish nation.Before they took flight, the Nazis organized a last execution on Jury 22, 1944: 286 prisoners were murdesed in the Castle. On that same day and on July 20, 1944, a further 800 prisoners were taken from the castle and executed at the  concentration camp in Majdanek, a suburb of Lublin.On July 22, 1944, of the Polish Committee for National Liberation (PKWN) was created under Soviet pressure. It assumed power over the territory of Poland which had been taken by the Red Army after the flight of the Nazis.Organized armed forces known as the Home Army, ‒ operated  in Poland  troughout the war. They were subordinate to the Polish Government in Exile, residing in England. The Government in Exile was recognized by all counties except the USSR. Home Army troops refused to submit to the Red Army and PKWN. For this reason, the Soviet and Polish army, together with security services, started to disarm the Home Army troop. Mass arrests and deportations into the USSR began.A number of Home Army units were disarmed, among them the famous 27th Infantry Division. Troughoot the Lublin District, mass arrests of Home Army soldiers took place. The detainees were sent to the former concentration camp in Majdanek and the Lublin Castle prison. Arrested were also state oflicials ‒ delegates of the Polish Government in London.The Commander of the Home Army Lublin District, General Kazimierz Tumidajski, was detained during negotiations with Soviet authorities and  deported to the USSR. Home Army soldiers who had been arrested and confined to Polish prisons, were subjected to investigations by the Soviet and Polish security service which involved the use of threats and a variety of tortures.  Describing his ordeal, one of the prisoners stated he could not relate “all the atrocities” he had suffered from Soviet officers. The detained soldiers received no medical assistance; those who managed to survive the Castle prison nightmare described the appearance of  battered Home Army soldiers and related their complaints.During the initial period discussed in this report, most Home Army soldiers were arrested by Soviet authorities without due judicial decision. They were interrogated in Russian, a language they did not speak. It was only 2 or 3 months later that the detainees were handed over to Polish authorities. Only then, Polish prosecutors issued formal decisions to remand them in custody, and the records of selected hearings were translated into Polish. The evidence gathered by Soviet security officers provided the grounds for indictments directed to military courts that operated in Lublin.            III. In 1944, the indictments signed by Polish military prosecutors were lodged with the Military Court of the Lublin Garrison, commanded by a Soviet officer, Colonel Konstantin Krukovsky.Preceding the first-instance hearing was a closed sitting where the court, composed of three judges, confirmed the indictment; the trial followed on that same day. The copy the indictment was delivered to the detainee only after the hearing had started.The main charges contained in indictments were: membership in the Home Army, unlicensed possession of firearms, or evasion of military service ‒ acts threatened with capital punishment. There is evidence to show that the actual penalties were decided upon by the Mi1itary Courts Department of the Polish Army, headed by a Soviet ofIicer, Brigadier General Alexander Tarnovsky. The execution of the orders was the responsibility of the head of the court, Colonel Krukovsky, and the judges presiding over the case.In none of the cases did the Lublin Garrison Military Court took any evidence whatsover, whether on motion of the defendant or on its own initiative. The only hearing of evidence consisted of hearing the defendant’s statement; the defendants admitted their membership of the Home Army but refused to acknowledge any guilt. The various formulations they used were then quoted out of context to prove they had in fact been guilty of trying to subvert democratic system of Poland ‒ an  assumption made well in advance.The trials were held at the Lublin Castle prison. They were closed sittings in which neither the counsel for the defence nor the prosecutor participated. The defendant’s family were not informed about the date of the trial as they knew nothing about his fate anyway, and the defendant himself did not learn about the trial until it started.Unqualified persons participated in deciding on conviction and sentence, or the court was formed inadequately. For example, the principle that the lay judges’ rank should not be lower than the defendant’s was commonly infringed upon. A glaring example of  such infringement was the case of Colonel Edward Jasiński who was convicted by N.C.O. lay judges.Delivering the judgment, the court informed the defendant that the decision was final and not subject to appeal. Most defendants were sentenced to death. Many meritorious Home Army soldiers who had fought for independence throughout the Nazi occupation met death this way.The sentences were carried out upon confirmation by the Commander-in-Chief of the Polish Army (at that time, General Michał Rola-Żymierski) or his second in command (Generals Świerczewski and Berling), and sometimes by lower rank commanders. They were obliged to examine the justification of the sentences ex officio; they also had the right to grant pardon.Confirmation of the sentence and pardon were two separate institutions of the law of criminal procedure; thus pardon could be granted even if the sentence had been confirmed. In practice, no rules whatsoever were observed: confirmed sentences were carried out without pardon proceedings, or following such proceedings but without the proceedings aimed at review of the grounds. It should be added that under the law in force, pardon could only be refused by the President of the National People’s Council, Bolesław Bierut, while the army commanders had merely the right to grant pardon. In fact, they also refused pardon on numerous  occasions.In practice, sentences were carried out basied on the order of Brigadier General Alexander Tarnovsky who informed the head of military court about the decision of Commander-in-Chief and ordered the need for immediate execution.Capital punishment was executed at the Castle prison, in the basement of the administration building, at various hours of day and night. The Report quotes the account of an execution provided by a surviving Lublin physician, and a numer of facts which, together with the now available reports from executions, tell about the identity of their participants. The grim record holders are two sergeants: within 50 minutes, one of them participated in the execution of 11, and the other one – of 12 Home Army soldiers.Until January 5, 1945, the bodies of the executed were secretly buried at a Lublin cemetery upon written of the prison warden Second Lieutenant Alojzy Stolarz; the orders have been preserved in the cemetery archives. There is no  mention at all about subsequent burials although – as follows from the attached documents – Home Army soldiers were still executed at the Castle after that date.The soldiers kept on their dignity till the end; scant accounts of their demeanour were provided by prison chaplains, the only persons the convict’s family about hos death.Throughout both the preparatory and the judicial proceedings, valid legal provisions were violated. The system of military penal law contained provisions dating from the 1930’s and not yet quashed at the time of examination of the discussed cases. Such provisions were simply treated as non-existent.The Code of Criminal Procedure and the Military Code of the Polish Armed  Forces in USSR, developed by the Political and Educational Board of the Polish  Army in the USSR established in 1943 was adopted as the legal grounds for proceedings. As shown by the facts quoted in this report, the summary procedure  was applied to defendants. It was provided for by the code of criminal procedure of the Polish Armed Forces in the USSR, but military courts competed with each other in breaking the law to the extent of not even observing the law that had been established in the USSR.Under the law then in force, none of the sentences discussed in the report ever became final and valid. Judicial proceedings glaringly infringed on all the principles of procedure: direct examination of evidence, impartiality, presumption of innocence, openness, adversary trial, right to defence, to appeal, and the right to apply for pardon.The Home Army soldiers mentioned in the report were convicted in defiance with the ban on retroactive force of law as the decree on  protection of state under which they were tried had entered into force on November 4, 1944 with the binding force since August 15, 1944; most had been imprisoned for many weeks before the decree was actually introduced.VII. The extermination of Home Army soldiers at the Lublin Castle was kept secret for decades. Many attempts at revealing the tragic events failed, and the demands for posthumous acquittal, made by families of the executed, were rejected.It was only after June 4, 1989, as a result of extraordinary appeals or re-institution of proceedings, that the Supreme Court passed many decisions on acquittal, manifesting not only the groundlessness of convictions but also their function as a political disposal of opponents of the new authority – of the Home Army formed by the legitimate Polish Government to fight the Nazi invaders.The enormity of lawlessness of the discussed practices made the Parliament of Republic of Poland pass, on February 23, 1991, an act on the invalidity of the judgments in cases of persons victimized for their activities on behalf of a sovereign Polish state.